2016
DOI: 10.1177/1099800416660760
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Biopsychosocial Investigation Into Head and Neck Cancer Caregiving

Abstract: Purpose Head and neck cancer (HNC) patients suffer from significant morbidity, which may introduce challenging care demands and subsequent stress-induced mind–body interactions for informal caregivers. This prospective study evaluated patient and caregiver predictors of diurnal cortisol rhythm among HNC caregivers during radiation treatment. Method Patient–caregiver dyads completed measures at radiation treatment start (T1; n = 32) and 5 weeks into treatment (T2; n = 29). Measures included the Functional Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Thomas and colleagues (2012) assessed CAR among spouses whose partners had prostate cancer and found that, although caregivers had a CAR of 13% compared with a CAR of 39% in control subjects, this difference was nonsignificant. In addition, diurnal cortisol slope became flatter (more dysregulation in cortisol rhythm) in caregivers in comparison to controls (Miller et al, 2002) and at 5 weeks postradiotherapy compared to the start of radiotherapy (Nightingale et al, 2017). When examining the relationships between cortisol levels and health outcomes in caregivers, Thomas et al (2012) found that lower cortisol levels were associated with the presence of post-traumatic stress disorder symptoms.…”
Section: Neuroendocrine Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thomas and colleagues (2012) assessed CAR among spouses whose partners had prostate cancer and found that, although caregivers had a CAR of 13% compared with a CAR of 39% in control subjects, this difference was nonsignificant. In addition, diurnal cortisol slope became flatter (more dysregulation in cortisol rhythm) in caregivers in comparison to controls (Miller et al, 2002) and at 5 weeks postradiotherapy compared to the start of radiotherapy (Nightingale et al, 2017). When examining the relationships between cortisol levels and health outcomes in caregivers, Thomas et al (2012) found that lower cortisol levels were associated with the presence of post-traumatic stress disorder symptoms.…”
Section: Neuroendocrine Functionmentioning
confidence: 96%
“…Miller 2014Longitudinal; T1 ¼ baseline, T2-T4 ¼ 2, 4, and 8 months; saliva collected upon awakening and 0.5, 1, 4, 9, and 14 hr after awakening quality of life (Nightingale et al, 2017) and depressive symptoms (Thomas et al, 2012). Cortisol was used as a biomarker to monitor the efficacy of interventions in five studies (Fancourt et al, 2016;Laudenslager et al, 2015;Lengacher et al, 2012;Pinar & Afsar, 2015;Walsh et al, 2007).…”
Section: Neuroendocrine Functionmentioning
confidence: 99%
“…There was a predominance of randomized clinical trials 4, 12-15 cross-sectional 4 and prospective studies 4. 20-3 The journal Cancer Nursig stood out, with three (20.0%) productions, 16,19,22 the language English, with 15 (100.0%) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and 2014, with five (33.0%). 12,15,[21][22]24 It was observed, as to the level of evidence, that most of the analyzed productions 8 (53.3%) presented evaluation 2C.…”
Section: P and I And Comentioning
confidence: 99%
“…12,15,[21][22]24 It was observed, as to the level of evidence, that most of the analyzed productions 8 (53.3%) presented evaluation 2C. [16][17][18][19][20][21][22][23][24][25][26] It was evidenced that the factors associated with the overload were related both to the clinical and cognitive conditions of the patients and the caregivers, being self-care deficit, care dependence, sleep alteration and psychosocial pressures prevalent. Among the manifestations of overload, stress, fatigue, exhaustion and intensification of depressive and anxious symptoms were identified.…”
Section: P and I And Comentioning
confidence: 99%
See 1 more Smart Citation